Hubungan Antara Penerimaan Kelompok Teman Sebaya dengan Prestasi Akademik Mahasiswa Pada Fakultas Ekonomi Universitas Negeri Jakarta - Ati Sumiyati; - Chairunnissa (Universitas Negeri Yogyakarta, 2010)
This research was purposed to obtain valid and reliable data about whether the peer group acceptance correlation with academic achievement.Data were collected using a survey on 78 students of Accounting Education Student at Faculty of Economics, Universitas Negeri Jakarta with a sampling technique using propotionate random sampling. The survey was conducted by distributing questionnaires to the samples who have determined. Scores of self report peer group acceptance report obtained by giving questionnaires with Likert type scale. While the academic achievement is used toindex the value of a Grade Point Average (GPA) students of the semester for about 5 semesters 089 093 during the academic year 2008 to 2011 of every subject. The regression equation in this research is Ŷ = 2.236 + 0.011X. From this equation, test requirements analysis conducted by the normality test error estimate the regression of Y on X obtained by test Liliefors Lo Lt (0.0628 0.1003). It mean the data are normally distributed. On the linearity The regression test we got the result Fh Ft (1.28 1.84) which can be concluded that the regression model is linear. As for the meaningful test obtained FhFt (23.58 4.00) which indicates that the regression equation is meaning. The test results by using the correlation coefficient of Pearson product moment values obtained rxy=0.494. This means there is a positive correlation between peer group acceptance with the academic achievement of students at Faculty of Economics, University of Jakarta. From the test calculations obtained thitung ttable, is 49561.69 indicating a significant correlation between variable X that is peer group acceptance a variable Y that is academic achievement. From the results obtained by calculating the coefficient of determination 24.4% so it can be said that the academic achievement variable Y is determined by the variable X peer group acceptance of 24.4%.